2015
DOI: 10.1002/acp.3166
|View full text |Cite
|
Sign up to set email alerts
|

Fading Affect Bias in the Philippines: Confirmation of the FAB in Positive and Negative Memories but Not for Death Memories

Abstract: SummaryEmotions associated with memories for the loss of a loved one and for negative events in general decrease in intensity more than memories associated with positive events, a phenomenon known as the fading affect bias (FAB). We tested whether FAB was cross‐culturally evident by collecting positive, negative, and memories for the deaths of loved ones from Filipinos. Memories were coded as violent/nonviolent and resolved/unresolved, and we predicted that resolved memories should show greater fading and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Given research conducted in the Philippines by Bond et al (2016), which showed no fading in death memories and fading in everyday negative memories, there should be a difference between memories for the loss of loved ones and everyday negative memories in ratings of emotional intensity at the event and currently by Mexicans. The researchers posit that emotional intensity in positive memories should remain relatively stable in intensity ratings at the time of the memory event and currently.…”
Section: Predictionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Given research conducted in the Philippines by Bond et al (2016), which showed no fading in death memories and fading in everyday negative memories, there should be a difference between memories for the loss of loved ones and everyday negative memories in ratings of emotional intensity at the event and currently by Mexicans. The researchers posit that emotional intensity in positive memories should remain relatively stable in intensity ratings at the time of the memory event and currently.…”
Section: Predictionsmentioning
confidence: 97%
“…As noted by Bond et al (2016), failure of the FAB to decrease the intensity of negative emotions is intrinsically tied to traumatic events that retain the initial emotional intensity due to their self-importance.…”
Section: Depression and Posttraumatic Stress Disorder As Moderators O...mentioning
confidence: 99%
“…Why is it important to conduct a cultural investigation centered on the exploration of emotional valence and intensity in memories of people who have endured a natural disaster, such as a super-typhoon? In a review of the FAB phenomenon and research that needs to be conducted on FAB, Skowronski et al (2014) noted that research has just now been emerging for cross cultural investigations of the FAB phenomenon (Bond et al, 2016;Ritchie, Batteson, et al, 2014;Skowronski et al, 2014) and that only one investigation by Bohn and Bernsten (2007) on memories for the fall of the Berlin Wall has assessed FAB in a flashbulb memory (FBM) for a significant event. No studies have looked at FAB in first-hand survivor memorial experiences in a disaster event.…”
Section: Fab Flashbulb Memories Near-death Experiences and First-hand...mentioning
confidence: 99%
“…The bulk of memories recalled by participants in these studies are fairly mundane, including events related to friendships, romantic relationships, work experiences, school experiences, and family related events. However, a few studies have examined the experience of the FAB using life-altering events such as the deaths of loved ones (Bond et al., 2016; Gibbons et al., 2016; Henderson et al., 2015). It remains to be seen whether emotional fading applies to first-hand experiences in large-scale events of national and personal tragedy, such as natural disasters.…”
Section: Remembering the Super-typhoon: Fading Affect Bias In Natural...mentioning
confidence: 99%
“…Conversely, the FAB is disrupted by unpleasant emotions, such as dysphoria [ 3 ], dispositional mood [ 22 ], and trait anxiety [ 23 ]. Although FAB research has examined the phenomenon in the context of death [ 8 , 24 , 25 ], it has not examined the relation of the FAB to grief for death events.…”
Section: Introductionmentioning
confidence: 99%